When Corporate Social Responsibility (CSR) Goes Wrong: a Second Assessment of the Integrated Waste Processing Plant TPST Samtaku in Jimbaran, Badung Regency - Podger, Owen Main (Universitas Ibn Khaldun Bogor, 2024)
The June 2023 edition of Astonjadro contained an article arguing that the Integrated Waste Processing Plant (Tempat Pengelolaan Sampah Terpadu, TPST) built in Jimbaran Bali provides a model for corporate social responsibility (CSR) (Okta Golden, 2023 April). The objective of this paper is to provide an alternative view from the neighboring community. The key methodology is a document review, of documents collected through action research by the author, until recently a resident suffering from the mis-location and mismanagement of the TPST, and active with the community in complaining and finally demanding its closure. The paper assesses the performance of applying for permission to build and operate the TPST, based on Indonesia Business Links principles of CSR, and assesses a failure in five of the seven principles. The paper questions the motives for inconsistencies and deceit uncovered, saying a response is beyond the scope of the paper. It sees Okta Golden, the author of the original paper, as a victim of the lack of social responsibility, It sees the regular requests for suffering neighbors to collaborate as inappropriate. It concludes that the assessment by Okta Golden that TPST Samtaku Jimbaran is a model of CSR was misplaced.